Atomic diffusion in liquid gallium and gallium-nickel alloys probed by quasielastic neutron scattering and molecular dynamic simulations - Shahzad, Anjum; Yang, Fan; Steffen, Julien; Neiß, Christian; Panchenko, Artem; Götz, Klaus; Vogel, Carola; Weißer, Matthias; Embs, Jan Peter; Petry, Winfried; Lohstroh, Wiebke; Görling, Andreas; et al. (Journal of Physics: Condensed Matter, 2024)
The atomic mobility in liquid pure gallium and a gallium-nickel alloy with 2 at% of nickel is studied experimentally by incoherent quasielastic neutron scattering. The integral diffusion coefficients for all-atom diffusion are derived from the experimental data at different temperatures. DFT-based ab-initio molecular dynamics (MD) is used to find numerically the diffusion coefficient of liquid gallium at different temperatures, and numerical theory results well agree with the experimental findings at temperatures below 500 K. Machine learning force fields derived from ab-initio molecular dynamics (AIMD) overestimate within a small 6% error the diffusion coefficient of pure gallium within the genuine AIMD. However, they better agree with experiment for pure gallium and enable the numerical finding of the diffusion coefficient of nickel in the considered melted alloy along with the diffusion coefficient of gallium and integral diffusion coefficient, that agrees with the corresponding experimental values within the error bars. The temperature dependence of the gallium diffusion coefficient D Ga ( T ) follows the Arrhenius law experimentally for all studied temperatures and below 500 K also in the numerical simulations. However, D Ga ( T ) can be well described alternatively by an Einstein-Stokes dependence with the metallic liquid viscosity following the Arrhenius law, especially for the MD simulation results at all studied temperatures. Moreover, a novel variant of the excess entropy scaling theory rationalized our findings for gallium diffusion. Obtained values of the Arrhenius activation energies are profoundly different in the competing theoretical descriptions, which is explained by different temperature-dependent prefactors in the corresponding theories. The diffusion coefficient of gallium is significantly reduced (at the same temperature) in a melted alloy with natural nickel, even at a tiny 2 at% concentration of nickel, as compared with its pure gallium value. This highly surprising behavior contradicts the existing excess entropy scaling theories and opens a venue for further research.
CRIS-Team Scopus Importer:2024-02-16
Keywords: ab-initio molecular dynamics; DFT-based machine learning force fields; gallium-nickel alloy; liquid gallium; quasielastic neutron scattering; self-diffusion

Effects of isotope and chemical incoherence on self-diffusion of atoms in liquid alloys of gallium with isotopes of nickel: Experiments based on quasielastic neutron scattering versus molecular dynamics simulations - Goychuk, Igor; Panchenko, Artem; Shahzad, Anjum; Fauser, Steffen; Neiß, Christian; Götz, Klaus; Vogel, Carola; Weißer, Matthias; Hakim, Bishoy; Embs, Jan Peter; Englhard, Jonas; Bachmann, Julien; et al. (Physical Review B, 2025)
Quasielastic neutron scattering (QENS) is a powerful experimental technique to investigate the diffusion of atoms in liquids. It relies on the fact that at low 𝑄 values essentially only incoherent scattering is observed from the diffusing atoms. In the case of alloys composed of two chemical elements, it is commonly believed that at low 𝑄 QENS mainly probes the self-diffusion of the element with a nonzero incoherent scattering cross-section, while the element with a zero incoherent scattering cross-section does not contribute. However, the findings of this study challenge this belief. The study examines alloys of natural gallium (which has a nonzero incoherent scattering cross-section) and isotopes 58 Ni and 60 Ni (both of which have a zero incoherent scattering cross-section). A crucial factor to consider here is chemical incoherence, which typically leads to the renormalization of the incoherent cross-sections of different chemical elements within a mixture. Unfortunately, this renormalization is often disregarded in an ad hoc manner. Significantly, the alloy containing 58 Ni shows a notable renormalization, scattering incoherently to a similar degree as natural nickel in a comparable alloy with equivalent concentrations of chemical elements. Similarly perplexing, natural nickel scatters with great intensity despite being predominantly composed of 58 Ni and 60 Ni (around 94% of the total). This behavior can be attributed to the accepted phenomenon of isotope incoherence. We calculate the integral diffusion coefficients of Ga and Ni atoms in various liquid alloys from QENS experiments. These values are then compared to the results obtained from corresponding molecular dynamics simulations conducted at various temperatures, taking into account chemical incoherence. The comparison shows good agreement within the range of errors for the Ga1−𝑥⁢ 58Ni𝑥 alloy at two concentrations (𝑥=0.02 and 𝑥=0.1). The agreement also partially holds for the Ga1−𝑥⁢Ni𝑥 alloy with natural nickel and for the Ga1−𝑥⁢ 60Ni𝑥 alloy, despite certain difficulties discusse
CRIS-Team Scopus Importer:2025-02-17
Keywords: Diffusion; Alloys; Liquid metals; Ab initio molecular dynamics; Molecular dynamics; Neutron scattering

Particle size segregation in granular pipe flow - Müller, Patric; Panchenko, Artem; Ku, Wing To; Pöschel, Thorsten (Chaos, 2025)
The flow of granular material through pipes is characterized by significant variations in solid fraction (density waves) along the pipe. Previously, it has been shown that this intermittent flow behavior can be mitigated by adding a texture to the pipe’s inner wall. This work shows that adding surface roughness can lead to particle size segregation as a side effect in bidisperse systems. Using particle simulations, we characterize the parameter ranges in which segregation occurs.
CRIS-Team Scopus Importer:2025-05-02